2008
DOI: 10.1021/am800027d
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion and Spreading Behavior on Vertically Aligned Silicon Nanowire Arrays

Abstract: In this report, we studied the interactions between biological cells and vertically aligned silicon nanowire (SiNW) arrays and focused on how SiNW arrays affected cellular behaviors such as cell adhesion and spreading. We observed that SiNW arrays could support cell adhesion and growth and guide cell adhesion and spreading behaviors. The results also showed that SiNW arrays could not only enhance the cell-substrate adhesion force but also restrict cell spreading. Combining the results from scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
191
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(202 citation statements)
references
References 21 publications
9
191
2
Order By: Relevance
“…Building on the previous observation that vertically grown NWs can support cell culture (15)(16)(17)(18)(19), we show that vertical NW substrates can serve as a universal, scalable, and highly efficient modality for introducing DNAs, RNAs, peptides, proteins, and small molecules into both immortalized and primary cell types, without chemical modification or viral packaging. This simplicity and generality, which stem from the direct physical access to the cell's interior afforded by NW penetration (15)(16)(17)(18)(19), make NW-based delivery distinct from chemical and viral methods that are widely employed (1)(2)(3)(4)(5)(6). Furthermore, this NW-based system is fully compatible with standard microarray printing techniques, allowing large collections of biomolecules to be delivered, or even codelivered, into live cells in a parallel and miniaturized fashion.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Building on the previous observation that vertically grown NWs can support cell culture (15)(16)(17)(18)(19), we show that vertical NW substrates can serve as a universal, scalable, and highly efficient modality for introducing DNAs, RNAs, peptides, proteins, and small molecules into both immortalized and primary cell types, without chemical modification or viral packaging. This simplicity and generality, which stem from the direct physical access to the cell's interior afforded by NW penetration (15)(16)(17)(18)(19), make NW-based delivery distinct from chemical and viral methods that are widely employed (1)(2)(3)(4)(5)(6). Furthermore, this NW-based system is fully compatible with standard microarray printing techniques, allowing large collections of biomolecules to be delivered, or even codelivered, into live cells in a parallel and miniaturized fashion.…”
mentioning
confidence: 53%
“…Previous studies have shown that vertical NWs spontaneously penetrate cells' membranes when cells are placed on top of the NWs (15)(16)(17)(18)(19). To visualize this penetration process, DiDmembrane-labeled HeLa cells (Magenta) were seeded on a bed of Si NWs whose gold tips had been prelabeled with This article contains supporting information online at www.pnas.org/cgi/content/full/ 0909350107/DCSupplemental.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The filopodia of cells on bare glass were thick and straight (Figure 2d), whereas those on SiNW substrates were thin and exhibited a unique behavior of wrapping around the nanowires regardless of the nanowire diameter (insets of Figures 2b and c). 28 As a result of this wrapping, the SiNWs were deflected by the cell filopodia, with the degree of bending depending on the diameter of the SiNW (Figures 2e and f). Furthermore, the number of filopodia of cells cultured on both SiNW substrates (N = 72 cells) was twofold that of cells grown on bare glass, as shown in Figure 2h.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Shalek et al reported the use of vertical silicon nanowires to deliver biomolecules such as proteins and DNA plasmids into living cells that grew attached to the nanowires (9). Together with other works that show vertical nanowires can support cell culture (10)(11)(12)(13)(14), these observations suggest a new and exciting possibility of using vertical nanowires as a universal platform to probe intracellular molecular events.…”
mentioning
confidence: 86%